Utilizing Media Network and Big Data on Presidential Election’s Winning: A Case Study - Sadri, Muhammad (International Journal Labs, 2023)
Background: Media and big data can be used as a political communication tool to win the presidential election, as in the case study of the Jokowi-Ma'ruf Amin pair who made optimal use of these two tools to win the 2019 presidential election contest. With big data, the successful team moves more efficiently and on target in attracting potential voters in the 2019 Presidential Election. Aim: To analyze the use of media networks and big data by the Jokowi-Ma'ruf Amin pair in the 2019 Presidential Election. Method: This study uses a qualitative descriptive approach with a literature study method. Self-study review dipakai penulis dalam menyajikan topik yang dibahas dengan pemahaman atas subjek penelitian. Findings: In the case study of the Jokowi-Ma'ruf Amin candidate pair, the utilization of media networks and the use of big data to map the battle areas in the 2019 Presidential Election contestation, has brought the candidate pairs Joko Widodo and Ma'ruf Amin (as political actors supported by party institutions) bearer politics) to be the winner in the political contestation. This is none other than because the success team of the Jokowi-Ma'ruf Amin candidate pair has paid attention to all aspects to win in the political contest, and took steps to involve media both digital and non-digital to the fullest, and utilized big data analysis in determining steps in the campaign.